Globalization : culture and education in the new millennium - Suárez-Orozco, Marcelo M., 1956-; Qin-Hilliard, Desirée (University of California Press, 2004)
Globalization defines our era. While it has created a great deal of debate in economic, policy, and grassroots circles, many aspects of the phenomenon remain virtual terra incognita. Education is at the heart of this continent of the unknown. This pathbreaking book examines how globalization and large-scale immigration are affecting children and youth, both in and out of schools.